Creating an electron-rich region on ultrafine Bi2O3 nanoparticles to boost the electrochemical carbon dioxide reduction to formate. Issue 1 (6th December 2022) - Zhan, Jiayu; Zhang, Lu-Hua; Wang, Xueli; Hu, Yuqi; Jiang, Yi; Yu, Fengshou
Abstract : Metal–support interfacial interactions can enrich the electron density of Bi2 O3 effectively facilitating *COO intermediate generation and boosting catalytic activity. Abstract : Various metal–support composites have been reported for the electrochemical CO2 reduction reaction (ECRR), while the effect of synergy between the size effect and interface regulation on ECRR performance is still rarely explored. Herein, we report ultrafine Bi2 O3 nanoparticles (∼1.9 nm) decorated on a nitrogen-vacancy-rich graphitic carbon nitride (Bi2 O3 /NV-C3 N4 ) electrocatalyst for highly efficient ECRR to formate. The Bi2 O3 /NV-C3 N4 electrocatalyst can achieve 95% formate selectivity at −0.9 V vs. RHE and 24 h long-term stability. Moreover, substantial formate selectivity (>80%) was gained over a wide potential range of more than 700 mV. The excellent performance was attributed to the electron transfer from NVs to Bi2 O3, forming an electron-rich region on Bi2 O3 and accelerating the electron transfer from Bi2 O3 to the adsorbed intermediates. This work provides a strategy for enhancing the catalytic activity of bismuth oxides to achieve a high efficiency for CO2 reduction to generate liquid products.